Pusat Kecantikan dan Kesehatan Wanita di Merauke (Arsitektur Simbolik Yin dan Yang) - Atiza Nurhuzna; Anton Topan; Yosi Valentina Simorangkir (Musamus Journal of Architecture, 2019)
Health and beauty of the body is the dream of all women, because beautiful and attractive appearance and a prime body will increase the confidence in the life of Sosalization. The demands for the maximum performance of today's urban lifestyle and the city of Merauke are one of them. With the beauty and health center of Women, the women in Merauke receive solutions for various beauty and women health problems, also get direct treatment with the best supporting facilities. With the theme approach of the symbolic architecture showing the balance between beauty and health (Yin and Yang) that can reflect the face of this woman's beauty and health center becomes a comfortable, healthy, and enjoyable place.Data retrieval methods with live observation, interviews, and documentation. The research site is located in several places, namely in the beautiful house on Jl. Martadinata, Merauke and at Salon Rudy at Jl. Raya Mandala, Merauke.The results of the research is a beauty center that caters to the needs of women needs in Merauke is a place to accommodate a wide range of beauty and women's health problems, also get centralized supporting facilities and Best. By using a symbolic architectural theme by taking the symbol Yin and Yang which is a symbol of balance so that the building can be integrated with the surrounding to provide comfort to the community.